The growth of firms, competition and maturity of industries - Bloch, Harry (School of Economics and Finance, Curtin Business School, 2005)
We develop a three-way categorization of capacity and its utilization covering micro, meso and macro framings, beginning with the approaches of Marshall, Steindl and Penrose. Within firms, we combine Steindl?s analysis on fixed capital with Penrose?s consideration of resources, including a higher-order form of capacity. We examine the implications of capacity expansion for competition and for the maturity of the industry, which reflects back on the value of the firm. We then argue that our higher-order concept of capacity can be made operational for empirical study by identifying a critical bottleneck that restrains firm growth at each point in its development.